Rare earth coordination dinuclear compounds constructed from 3,5-dicarboxypyrazolate and succinate intermetallic bridges - Lahoud, Marcelo G. [UNESP]; Muniz, Elaine C. [UNESP]; Arroyos, Guilherme [UNESP]; Fávaro, Marcelo A. [UNESP]; Davolos, Marian R. [UNESP]; D'Vries, Richard F.; Ellena, Javier; Freitas, Rafael S.; Arrighi, Everton; Frem, Regina C. G. [UNESP] (Royal Society of Chemistry (RSC), 2016)
In this paper we describe the synthesis of a new family of rare earth compounds of general formula [RE2(dcpz)2(suc)(H2O)8]·(H2O)1.5, where RE = Y (1), La (2), Ce (3), Pr (4), Nd (5), Sm (6), Gd (7), Tb (8), Dy (9), Ho (10), Er (11), Tm (12) and Yb (13); dcpz = 3,5-dicarboxypyrazolate; suc = succinate. Single crystal X-ray diffraction studies showed that all the complexes are isostructural and crystallize in the triclinic system, space group P1. They exist as dinuclear discrete molecules in which the metallic centers are linked together by dcpz and suc bridges. Hydrogen bonds between dimers give rise to a 3D bcu supramolecular network with topology (424·64). Solid-state photoluminescence studies revealed that the ligand-to-metal energy transfer mechanism is responsible for the visible emission of Sm (6), Tb (8) and Dy (9) compounds while for (5), near-infrared (1060 nm) emission was obtained by the direct excitation f orbitals in the Nd3+ ion. Magnetization measurements indicated antiferromagnetic interactions between the RE3+ ions, except Y3+ (1) and La3+ (2).